FISH-MAKHANA (EURYALE FEROX SAUSB) INTEGRATION- A CASE STUDY OF SUSTAINABlE AQUAFARMING SYSTEM IN NORTH BIHAR - Verma, Anand Mohan; Jha, V.; Ahmad, S. H. (Journal of Indian Fisheries Association, 2008)
The paper deals with a technique to synchronize two crops, fish and makhana (Euryale ferox Salisb) in a pond. In such eco-friendly integration both crops are mutually benefited. Decomposed plant parts of makhana crop form organic matter that releases nutrients in the water to enhanceplankton population. Organic detritus not only acts as food for bottom dwelling fishes (mrigal and common carp) but also provides a suitable substratum for the growth of zooplankton, insect larvae, nematodes and gastropods. Fishes contribute to the control of makhana pests. Theirfaecal matter acts as organic manure for makhana crop. Plankton population fluctuated between 1260 u/1 to 4030 u/1 in the control pond and 1630 u/1 to 4722 u/1 in the experimental pond. During the grand growth period of makhana crop(April to July} the dissolved oxygen content fluctuated between 5.02 mg/1 to 6.68 mg/1 in the covered areas and 6.04 mg/1 to 6.92 mg/1 in uncovered areas. Makhana leaves acting as blanket barrier over the water surface brought down the D.O.content in the covered areas of the pond. Free C02 content showed wider fluctuation in the experimental pond (25.2 mg/1 to 30.9 mg/1) than in the control pond.{25.1 mg/1 to 28.6 mg/1). This could be due to decomposition of plant parts of the presiding crop lying as debris at the pond bottom. Autochthonous supply of nutrients enhanced the content of Nitrogen, Phosphorous and Organic Carbon in the soil of experimental pond. The experimental pond covering an area of 0.40 ha yielded 852 kg fish and 200 kg pops whereas the control pond covering the same area produced 777 kg fish only. The net profit per ha came out to be Rs.1,04,700 and Rs. 66,200 in integrated and non-integrated system respectively. Owing to crop diversification, the present integrated systemwas found to be more viable than the non-integrated system in terms of production and net profit.Key Words: fish- Makhana (E.ferox, Salisb), Integration, Aquafarming, North Bihar.